Evaluation (Scottish Historical and Archaeological Internet Reports, 2010)
Evaluation in 1994 located two previously unknown sites (two ring-groove structures with associated negative features and an enigmatic area of rough paving) and confirmed the existence of a third thought to have been destroyed (remains of the engine house associated with Fuffet coal pit). In addition, numerous field drains were revealed. Further evaluation in 2005 and 2006 added little to the original results. Full details are held in the RCAHMS archive.